Low Dose Methotrexate and Vinblastine, Given Weekly to Patients With Desmoid Tumours, is Associated With Major Toxicity. (2003) - van der Hul, René L.; Seynaeve, Caroline; van Geel, Bert N.; Verweij, Jaap
Abstract : Purpose: To evaluate the tolerance of a low dose chemotherapy regimen for desmoid tumours. Patients and methods: Patients with desmoids for whom radical resection was impossible or related to extensive mutilation were treated with chemotherapy. Treatment consisted of intravenous methotrexate at a dose of 50mg and vinblastine at a dose of 10mg weekly, scheduled to be given for a total period of 1 year. Doses were reduced and/or delayed on an individual basis, depending on the observed type of toxicity. Results: Ten patients (six males; four females), median age 43 years (range17–75), median WHO performance score 1 (range 0–1), were treated. None of them was able to complete the treatment as scheduled, due to observed side effects, while in two patients treatment was also discontinued because of progressive disease. In six patients, less than 50% of the projected administrations and dose could be given. Severe organ toxicity was noted in three patients (one interstitial pneumonitis, two toxic hepatitis), which, however, was reversible in all cases. Discussion: Methotrexate and vinblastine given at this dose and schedule lead to an unacceptable level of toxicity for a long-term treatment, and cannot be recommended for standard use.